Autophagy protects gastric mucosal epithelial cells from ethanol-induced oxidative damage via mTOR signaling pathway. Issue 10 (May 2017) - Chang, Weilong; Bai, Jie; Tian, Shaobo; Ma, Muyuan; Li, Wei; Yin, Yuping; Deng, Rui; Cui, Jinyuan; Li, Jinjin; Wang, Guobin; Zhang, Peng; Tao, Kaixiong
Alcohol abuse is an important cause of gastric mucosal epithelial cell injury and gastric ulcers. A number of studies have demonstrated that autophagy, an evolutionarily conserved cellular mechanism, has a protective effect on cell survival. However, it is not known whether autophagy can protect gastric mucosal epithelial cells against the toxic effects of ethanol. In the present study, gastric mucosal epithelial cells (GES-1 cells) and Wistar rats were treated with ethanol to detect the adaptive response of autophagy. Our results demonstrated that ethanol exposure induced gastric mucosal epithelial cell damage, which was accompanied by the downregulation of mTOR signaling pathway and activation of autophagy. Suppression of autophagy with pharmacological agents resulted in a significant increase of GES-1 cell apoptosis and gastric mucosa injury, suggesting that autophagy could protect cells from ethanol toxicity. Furthermore, we evaluated the cellular oxidative stress response following ethanol treatment and found that autophagy induced by ethanol inhibited generation of reactive oxygen species and degradation of antioxidant and lipid peroxidation. In conclusion, these findings provide evidence that ethanol can activate autophagy via downregulation of the mTOR signaling pathway, serving as an adaptive mechanism to ameliorate oxidative damage induced by ethanol in gastric mucosal epithelial cells. Therefore, modifying autophagy may provide a therapeutic strategy against alcoholic gastric mucosa injury. Impact statement: The effect and mechanism of autophagy on ethanol-induced cell damage remain controversial. In this manuscript, we report the results of our study demonstrating that autophagy can protect gastric mucosal epithelial cells against ethanol toxicity in vitro and in vivo . We have shown that ethanol can activate autophagy via downregulation of the mTOR signaling pathway, serving as an adaptive mechanism to ameliorate ethanol-induced oxidative damage in gastric mucosal epithelial cells. This study brings new and important insights into the mechanism of alcoholic gastric mucosal injury and may provide an avenue for future therapeutic strategies.